Association Between Diabetes Mellitus and All-Cause and Cardiovascular Mortality Among Individuals With Ultrasound-Defined Non-Alcoholic Fatty Liver Disease - Wu, Weiti; Xiang, Jingjing; Chen, Xiaoye (Frontiers in Endocrinology, 2021)
Objective: The influence of diabetes on mortality among patients with nonalcoholic fatty liver disease (NAFLD) in the general population has not been extensively studied. This study aimed to determine the relationship between diabetes and all-cause and cardiovascular mortality in patients with hepatic ultrasound-confirmed NAFLD using data from the Third National Health and Nutrition Examination Survey (NHANES III), 1988–1994. Methods: Data from 4037 adult individuals with NAFLD from the NHANES III and mortality outcomes linked to National Death Index records through December 31, 2015, were included. Cox proportional hazard models were used to calculate hazard ratio (HR) and corresponding 95% confidence interval (CI) for mortality from all causes and cardiovascular disease after adjusting for multiple variables. Results: Among 4037 subjects with NAFLD (55.9% female), 483 had diabetes at baseline. During a median follow-up of 22.1 years, 1517 (11.5%) died, including 332 (8.22%) from cardiovascular causes. Diabetes was associated with increased all-cause (HR 3.02 [95% CI 2.67–3.41]) and cardiovascular (HR 3.36 [95% CI 2.61–4.32]) mortality in an unadjusted multivariable Cox regression model. The association remained statistically significant after adjusting for a range of potential confounders (HR 2.20 [95% CI 1.90–2.55] for all-cause mortality, and HR 2.47 [95% CI 1.81–3.37] for cardiovascular mortality). An additional stratified analysis did not reveal significantly altered results. Conclusion: Diabetes was associated with all-cause and cardiovascular mortality in patients with NAFLD. This link could be further characterized in future studies assessing the degree of glycemic control and its relationship with mortality in patients with diabetes and NAFLD.